Fucoidans from Brown Alga Fucus evanescens: Structure and Biological Activity - Menshova, Roza V.; Shevchenko, Natalia M.; Imbs, Tatiana I.; Zvyagintseva, Tatiana N.; Malyarenko, Olesya S.; Zaporoshets, Tatyana S.; Besednova, Natalia N.; Ermakova, Svetlana P. (Frontiers in Marine Science, 2016)
Brown alga Fucus evanescens, widespread in the Far Eastern seas of Russia, is valuable source of sulfated polysaccharides – fucoidans with beneficial biological activities. The most homogenous fraction of fucoidan from F. evanescens was shown to be molecule containing linear main chain of alternating 2-sulfated 1,3- and 1,4-linked α-L-fucose residues. Few sulfate groups were found in position 4 of some 1,3-linked fucose residues. Acetyl groups occupied free C-3 of 1,4-linked residues and/or the C-4 of 1,3-linked fucose residues. Enzymatic hydrolysis, mild acid hydrolysis and autohydrolysis of native fucoidan were used for elucidation of the fine structural characteristics of fucoidan from F. evanescens. The aim of this review to summarize published data on biological activities of fucoidan from F. evanescens: antiviral, anticoagulant, thrombolytic, hepatoprotective, immunomodulatory, anticancer, and their practical application.